2010
DOI: 10.1093/jac/dkq005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bloodstream infection with Klebsiella pneumoniae producing VIM-1 metallo- -lactamase

Abstract: Stay in an ICU, prior use of carbapenems and prior exposure to >3 different classes of antibiotics were independent predictors for VPKP BSIs. These findings provide guidance for antibiotic policies and infection control strategies to contain the spread of VPKP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 13 publications
2
19
0
2
Order By: Relevance
“…Other studies reported that the administration of almost all broad-spectrum antibiotics and not just carbapenems could facilitate the development of infections due to CRKp or CRE in general. 24,25 The mortality rate in this study was high for patients with both CRKp and CSKp infections. Notably, 21% of them died within 2 days from the onset of the infection.…”
Section: Discussionmentioning
confidence: 70%
“…Other studies reported that the administration of almost all broad-spectrum antibiotics and not just carbapenems could facilitate the development of infections due to CRKp or CRE in general. 24,25 The mortality rate in this study was high for patients with both CRKp and CSKp infections. Notably, 21% of them died within 2 days from the onset of the infection.…”
Section: Discussionmentioning
confidence: 70%
“…Several investigators have evaluated the factors associated with increased risk for acquisition of CPE in the hospital setting (69,91,98,106,117,132,205,233,261). Investigators from Israel have shown that poor functional status of the host, prior antibiotic therapy, and stay in the ICU are independent risk factors for colonization or infection with carbapenem-resistant K. pneumoniae (233).…”
Section: Cpe In Health Care Settings Epidemiologymentioning
confidence: 99%
“…Case-control studies have shown that almost every class of antibiotics can select for CPE (69,91,98,117,120,132,203,261). What appears to be more important, however, is the cumulative number of prior antibiotic exposures rather than the use of a specific class of antibiotics (69,205). Since members of the Enterobacteriaceae constitute part of the human enteric flora, once CPE colonize the intestinal tract, carriage may persist for a long time (232).…”
Section: Cpe In Health Care Settings Epidemiologymentioning
confidence: 99%
“…[82][83][84][85][86][87][88][89][90] Are carbapenems the drugs of choice for the treatment of invasive infections caused by ESBL-producing Enterobacteriaceae?…”
Section: Therapymentioning
confidence: 99%